In silico identification of compounds from Piper sarmentosum Roxb leaf fractionated extract inhibit interleukin-6 to prevent rheumatoid arthritis - Dao, Tran Nhat Phong; Onikanni, Sunday Amos; Fadaka, Adewale Oluwaseun; Klein, Ashwil; Tran, Van De; Le, Minh Hoang; Wang, Chih-Hao; Chang, Hen-Hong (Frontiers in Pharmacology, 2024)
Objective: Medicinal herbs with a phytonutrient background has been applied globally as major alternatives to ameliorate the continuous increase in rheumatoid arthritis cases worldwide. We herein aimed to critically examine the bioactive components of the medicinal herb Piper sarmentosum Roxb leaf fractionated extract for its potential to inhibit the influx of interleukin-6 (IL-6) in rheumatoid arthritis. Methods: Therefore, the Schrödinger platform was employed as the main computational acumen for the screening of bioactive compounds identified and reference compounds subjected to molecular simulation (MDS) for analyzing the stability of docked complexes to assess fluctuations and conformational changes during protein–ligand interactions. Results: The values of the simulatory properties and principal component analysis (PCA) revealed the good stability of these phytochemicals in the active pocket of interleukin-6 (IL-6). Discussion: Our findings reveal new strategies in which these phytochemicals are potential inhibitory agents that can be modified and further evaluated to develop more effective agents for the management of rheumatoid arthritis, thereby providing a better understanding and useful model for the reproduction and/or discovery of new drugs for the management of rheumatoid arthritis and its complications.